KAJIAN EKONOMI USAHATANI SAYUR DAUN-DAUNAN (LEAVY VEGETABLES) DI KABUPATEN ENDE - Philipus Nerius Supardi; Charly Mutiara (Agriculture Faculty of Flores University, 2018)
Economic Study of Leaf Vegetable Farming and Vegetable Marketing Channel Systems in Ende Regency.This study aims to conduct an economic study of leaf vegetable farming and vegetable marketing channel systems in Ende Regency. This research was carried out in several sub-districts which were the center of vegetable production in the traditionally cultivated Regency of Ende. The sub-districts that were the object of research were Kelimutu Subdistrict, Lepembusu Kelisoke, Detusoko, Wolojita. The observation variables in this study were farming income, farming costs, economic life of farming, and vegetable distribution systems. Variable analysis using financial analysis was used to determine the criteria for evaluating investment feasibility of vegetable farming. This financial analysis uses NPV and B / C Ratio. Based on the results of the research that has been done, it can be concluded that the B / C ratio is 12.6, which means that the vegetable farms of Ende District respondent farmers deserve to continue to be cultivated. While the NPV value is Rp. 20,912,730.34. Vegetable distribution of leaves of respondent farmers in Ende district using a direct sales system to retailers on the market. Based on the values ??obtained, the vegetable farms of farmers in Ende Regency are worthy to continue.